Detection of Liquid Explosives and Flammable Agents in Connection with Terrorism - Kuznetsov, Andrey (Springer, 2017)
The Terrorist Pallet of Liquid Explosives and Flammable Fuels -- Overview of Liquid Explosives’ Detection -- Chemistry and Properties of Liquid Explosives...